2015
DOI: 10.1111/jfr3.12174
|View full text |Cite
|
Sign up to set email alerts
|

Flood damage assessment in the Pampanga river basin of the Philippines

Abstract: In this study, a flood damage assessment method was proposed for the assessment of flood risk in data-poor river basins by using a physical-based numerical model, satellite-based information and socio-economic factors. The Pampanga river basin of the Philippines was selected for the case study. For the flood damage assessment, hazard characteristics, such as flood depth and duration, were computed using the rainfall runoff inundation model. Agriculture and households, which are major exposures in flood-prone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 9 publications
0
60
0
Order By: Relevance
“…In Candaba, residences concentrated in the western part of the municipality sustain frequent moderate inundation. In some flood‐prone villages, many people live in two‐story residences or elevated houses with silts to reduce potential damages during regular floods (Juarez‐Lucas et al, ; Shrestha et al, ). Damage analyses of the 2011 floods, for instance, report mean damages of US $1,245 to residential buildings and households assets in Candaba (Shrestha et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Candaba, residences concentrated in the western part of the municipality sustain frequent moderate inundation. In some flood‐prone villages, many people live in two‐story residences or elevated houses with silts to reduce potential damages during regular floods (Juarez‐Lucas et al, ; Shrestha et al, ). Damage analyses of the 2011 floods, for instance, report mean damages of US $1,245 to residential buildings and households assets in Candaba (Shrestha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In some flood‐prone villages, many people live in two‐story residences or elevated houses with silts to reduce potential damages during regular floods (Juarez‐Lucas et al, ; Shrestha et al, ). Damage analyses of the 2011 floods, for instance, report mean damages of US $1,245 to residential buildings and households assets in Candaba (Shrestha et al, ). Similarly, by assessing only benefits from wild fish capture and rice agriculture we address only a portion of benefits derived from the use of flood‐prone land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RRI model setup and its equations are explained in Sayama [26,54]. The various applications of the RRI model in hydrological studies can be found in several studies [26,41,54,58,59]. The model equations are derived based on the following mass balance Equation (1) and momentum Equations (2) and (3) for gradually varied unsteady flow:…”
Section: Rri Modelmentioning
confidence: 99%
“…The damage was the sum of the cost of sediment removal (cleaning) and the loss of crops, which changed according to the growth phase. Depth-damage curves for crops can be found in different studies (CEIWR-HEC, 1985;Hansen, 1987;Shrestha et al, 2015). Owing to modelling on a mesoscale, our approach was simpler: we set a threshold value of water depth that causes total crop damage.…”
Section: Model Structurementioning
confidence: 99%